Fração de excreção de sódio, osmolaridade e densidade urinária em recém-nascidos prematuros alimentados com leite humano de banco adicionado de suplemento - Tanaka, Atsuko; Rugolo, Ligia Maria Suppo de Souza [UNESP]; Miranda, Antero F. M. [UNESP]; Trindade, Cleide E. P. [UNESP] (Fundacao Sociedade Brasileira de Pediatria, 2006)
Objective: This research was performed with the objective of investigating the renal effects on premature newborn infants of fortifying banked donor human milk. Methods: Clinical intervention trial, of the before-and-after type, involving 28 premature newborn infants split into two groups by postconceptional age at the start of the study: GI < 34 weeks (n = 14) and GII ≥ 34 weeks (n = 14), and assessed at three sample points: S1, on unfortified donor human milk, S2, after 3 days, and S3, after 10-13 days on fortified donor human milk. Nutrient intake, weight gain, fractional sodium excretion, urinary osmolality and specific density were compared with two-way ANOVA for repeated measures. Results: Fluids, energy and sodium intakes were similar for both groups, and weight gain was satisfactory. Among the preterms with < 34 weeks postconceptional age, serum sodium was lower at the end of the study and the fractional sodium excretion was elevated at the start and at the end of the study (S1 = 2.11±1.05; S2 = 1.25±0.64; S3 = 1.62±0.88), with a significant difference in relation to GII (S1 = 1.34±0.94; S2 = 0.90±0.54; S3 = 0.91±0.82). Osmolality and urinary specific density were normal, with no differences between groups or collection dates. Conclusions: No adverse effects on the renal function of these preterms were detected as a result of being fed fortified donor human milk. Copyright © 2006 by Sociedade Brasileira de Pediatria.
Fractional sodium excretion, urinary osmolality and specific gravity in preterm infants fed with fortified donor human milk
Keywords: analysis of variance; breast milk; caloric intake; clinical article; controlled study; fluid intake; human; newborn; nutrient uptake; prematurity; relative density; sodium excretion; sodium intake; urine osmolality; weight gain; Analysis of Variance; Calcium, Dietary; Food, Fortified; Gestational Age; Humans; Infant; Infant Formula; Infant, Newborn; Infant, Premature; Infant, Very Low Birth Weight; Milk, Human; Osmolar Concentration; Phosphorus, Dietary; Sodium; Sodium, Dietary; Specific Gravity; Urine; Weight Gain